Integration of stability model of PV system by using WEEC model and generic type 4 PV model in PSSE software / Mohammad Nayeim Fazumy Mohd Tajudin, Mohd Naji Mohd Hussain and Mashitah Mohd Hussain - Mohd Tajudin, Mohammad Nayeim Fazumy; Mohd Hussain, Mohd Najib; Mohd Hussain, Mashitah (UiTM Press, 2023)
When a huge generation of power is generating from the solar power plant to the grid interconnection, the system tends to create a stability problem and thus disrupted the grid system in disturbance issues such as bus fault, line fault and tripping. This sudden disturbance and irradiance drop occurrence is tended to interrupt the stability of the system from providing balance electrical production within the electrical grid. The level of photovoltaic (PV) penetration also influences the constancy of the system longer duration critical clearing time (CCT) of the system fault occurrence back to its normal condition. This paper presents the development of PV plant model for dynamic stability assessment using the Siemens Power System Simulation for Engineering (PSSE) software. A dynamics response from simulation is used to investigate the stability and behaviour of PV plants in grid interconnection by constructing a 30-bus system in the PSSE using two types of PV generators and observe the system's behaviour where it reaches its stability.